Hubungan Status Maternal Dengan Tingkat Kecemasan Dalam Menghadapi Sectio Caesarea - Zuhroh, Diah Fauzia; Hambali, Hambali (Universitas Muhammadiyah Gresik, 2022)
ABSTRACT Childbirth sometimes cannot be passed normally, so it have to undergo cesarean section with the incidence of Sectio caesarea reaches 95.3% in East Java, and 49% of surgical cases at Prima Husada Hospital during 2021. This surgery has an impact that can cause anxiety in the mother. This study aims to analyze the relationship between maternal status and maternal anxiety in dealing with cesarean delivery at Prima Husada Hospital Surabaya. The methods use analytical descriptive research design with a cross sectional approach. The total population of 202 mothers was calculated in 1 year. The sample size used accidental sampling technique so that 18 mothers were obtained within 1 month. The variables used are maternal status and anxiety. The instrument used is a questionnaire and the Zung Self Anxiety Scale. The result showed that maternal status both of primigravida and multigravida were 9 (50%) mothers. Almost all mothers experienced normal levels of anxiety as many as 15 (83.3%) mothers. Based on the Contingency Coefficient test analysis, the statistical test value p value was 0.058 (p > 0.05). So, the conclusion of this study is there is no Relationship between Maternal Status and Maternal Anxiety Levels in Facing Sectio caesarea Delivery at Husada Prima Hospital Surabaya.